The role of SELENBP1 and its epigenetic regulation in carcinogenic progression - Zhang, Yue; He, Qing (Frontiers in Genetics, 2022)
The initiation and progression of cancer is modulated through diverse genetic and epigenetic modifications. The epigenetic machinery regulates gene expression through intertwined DNA methylation, histone modifications, and miRNAs without affecting their genome sequences. SELENBP1 belongs to selenium-binding proteins and functions as a tumor suppressor. Its expression is significantly downregulated and correlates with carcinogenic progression and poor survival in various cancers. The role of SELENBP1 in carcinogenesis has not been fully elucidated, and its epigenetic regulation remains poorly understood. In this review, we summarize recent findings on the function and regulatory mechanisms of SELENBP1 during carcinogenic progression, with an emphasis on epigenetic mechanisms. We also discuss the potential cancer treatment targeting epigenetic modification of SELENBP1, either alone or in combination with selenium-containing compounds or dietary selenium.